Producción de Biol a partir de cuatro fuentes de materia orgánica en el fundo Cacatachi UNSM - T - Flores del Águila, Manfred Jhosset (2009)
This present report entitled "Biol production from four sources of organic matter in the farm Cacatachi - Tarapoto - founded as San Martin - Peru", is aimed to identify the production and physical-chemical characteristics of Biol obtained from the nutritional richness of 4 organic matter sources and make the economic analysis of the tested treatments. The research work was conducted at the farm Cacatachi of the National University of San Martín - Tarapoto, km 8, to the left of the road Fernando Belaunde, Tarapoto-Moyobamba, over a period of 3 months. Descriptive statistics were applied, their experimental units cover five treatments in 4 repetitions, and utilized inputs were: manure of cattle, sheep, pork, chicken. The obtained results of this research work indicate that with respect to the amount of biol produced, the treatments in T2 and T3 had the same amount in comparison with treatments T1 and T4, referring to the physical and chemical analysis, the T1 obtained (2.5%), of nitrogen content, T3 (0.25%) in phosphorus, treatment T4 (1.9%) in potassium, (0.13%) in calcium and (0.008%)magnesium; regarding to the relationship Cost/benefit doesn`t exists loss in any of the treatments.